Leveraging Social Media to Enhance English Language Learning Effectiveness: Insights from the Implementation of the Independent Curriculum in Banyuwangi Regency - Doni Hadi Irawan; Suwarso Suwarso; Janoko Janoko; Muhamad Alfi Khoiruman (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the role of social media in enhancing the effectiveness of English language learning within the implementation of the Merdeka Curriculum in Banyuwangi Regency. With its emphasis on flexible and student-centered learning, the Merdeka Curriculum opens opportunities for integrating familiar digital platforms into classroom instruction. A mixed-methods approach was employed, combining qualitative and quantitative techniques. Qualitative data were collected through classroom observations, teacher interviews, and content analysis to examine how social media is utilized in learning. Quantitative data were gathered using statistical analysis to measure the impact of social media use on students' English learning outcomes. The findings indicate that platforms such as Facebook, Instagram, and YouTube significantly enhance student engagement and motivation. Observational data revealed increased enthusiasm and active participation when materials were delivered through familiar social media platforms. Teachers reported improved student interaction in online discussions and greater involvement in assignments shared digitally. Furthermore, students benefited from expanded access to learning materials beyond formal class hours, leading to improved comprehension and language skills. The integration of social media into English learning supports the Merdeka Curriculum’s goals by fostering active, collaborative, and personalized learning experiences. It not only aligns with students' daily digital habits but also contributes to improved learning outcomes. This research highlights the potential of social media as an innovative educational tool to create more dynamic, relevant, and responsive learning environments.